CONSTRUCTION OF NEURAL NETWORKS FOR CLASSIFICATION POINTS OF LINEAR COMPLEX OF PLANES OF GENERAL TYPE - Anatoliy Nicolaevich Makoha; Tatyana Evgenjevna Tyshlyar (Вестник Северо-Кавказского федерального университета, 2022)
The work describes the construction, training and testing of an artificial neural network (ANN) designed for determining whether an arbitrary point a seven-dimensional projective complex spacebelongs to the variety of singular points of the first kind for linear complex of planes of general type. This complex does not admit the singular points of the second kind and the completely singular planes.